Analysis of PM Dispersion and Source Identification in Jl. Soekarno-Hatta, Pekanbaru, using HYSPLIT - Mustaqiman, Aulia Nur (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study investigates the spatiotemporal characteristics of PM pollution in Jl. Soekarno-Hatta, Pekanbaru, Indonesia, during January to November 2024, integrating air quality monitoring data, meteorological analysis, and HYSPLIT trajectory modeling. The highest PM concentration was recorded on 22–23 September 2024 at 55.74 µg/m³, corresponding to an AQI of 131, classified as “Unhealthy for Sensitive Groups.” Monthly averages ranged from 18 µg/m³ in January to 56 µg/m³ in September. A total of 37 days exceeded 50 µg/m³, and 112 days surpassed the U.S. EPA’s moderate threshold of 35 µg/m³. Meteorological data showed that low wind speeds (2.3–2.7 kph), persistent humidity (76–82%), and nighttime temperature inversions contributed to pollutant accumulation. Rainfall exhibited a strong inverse correlation with PM, with the driest month (June, 110 mm) aligning with high PM levels, and the wettest (November, 312 mm) aligning with lower concentrations ( 21 µg/m³). HYSPLIT backward trajectory modeling revealed that air masses originated from the northwest, indicating contributions from transboundary sources such as peatland fires in West Sumatra. Forward trajectories showed that pollutants from Jl. Soekarno-Hatta, Pekanbaru, could reach Jambi and South Sumatra. The findings highlight the need for integrated air quality strategies, including emission reduction, fire prevention, and early warning systems, to mitigate PM exposure and protect vulnerable populations in tropical urban environments.